Edukasi Pertolongan Gawat Darurat Cedera Ekstremitas Atas Dengan Teknik Balut Bidai Terhadap Pengetahuan Remaja Di MA Al-Ittihadiyah Pangkalan Masyhur Medan - Huwaina Af’idah; Erita Gustina; Endang Roswati Simamora; Erica L. Nababan; Halasan L. Simamora (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
The increase in mortality rates, caused by traffic accidents, usually occurs partly because Indonesians do not know how to provide proper first aid when victims are found (Ferianto, 2023). Injuries to the musculoskeletal system must be treated quickly and appropriately, because if it is too late, it will cause the condition of the injury to worsen and cause bleeding. The purpose of this study was to determine the effect of education on emergency assistance for upper extremity injuries with splinting techniques on adolescent knowledge. This research method uses a quantitative design using pretest and posttest questionnaires. The administration of pre-test and post-test questionnaires is according to the number of participants who participated in the education. The number of samples obtained in this study was 40 people with the target of MA adolescents with an age range of 15-17 years. This study was conducted on July 25, 2025, at MA Al-Ittihadiyah Pangkalan Masyhur Medan. The results of this study showed a significant difference between the level of knowledge before (pre-test) and after (post-test). Conclusion: The results of this study indicate that there is an effect of emergency aid education for upper extremity injuries using splinting techniques on the knowledge of adolescents at MA Al-Ittihadiyah Pangkalan Masyhur Medan.